If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 17 = 62 Reorder the terms: 17 + 3y = 62 Solving 17 + 3y = 62 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 3y = 62 + -17 Combine like terms: 17 + -17 = 0 0 + 3y = 62 + -17 3y = 62 + -17 Combine like terms: 62 + -17 = 45 3y = 45 Divide each side by '3'. y = 15 Simplifying y = 15
| y+19=192 | | f(-6)=7-2x | | 4x+14=5x | | 2x=6(2x-2)-5 | | 13.62+.13(x+3)=14.37+.09x | | 3(3+1)=(9-2x) | | 6n=(n+5) | | 30=-8x+2(x-6) | | y=mx+bfindx | | x^1/4=2 | | 5x-15=2x+20 | | 90+3+x+x-8=180 | | 10n-0.75=0.1n-0.375 | | 2-7g=2-g | | 2e^3x-9=0 | | 12a=3a+2.5a+a | | -1=6x-31 | | 15.93+.09(x+3)=16.43-.13x | | -3(3y-7)+2(2y+8)= | | 2[-2(4x+5)+4(3x-4)]= | | z/3=11 | | 5x-7=2x-14 | | 7/3.7/5 | | 51=50 | | (x/3)-9= | | -7y-12w=29 | | (-3/7)÷(-14/11) | | -5y-8=-3y+2 | | (4y^2+2y+1)-(y^2-9)= | | 13/11-(-1/7) | | 22x+8=-80 | | -3(4y-9)+2(3y+5)= |